The “national identity” clause enshrined in Article 4(2) of the Treaty on European Union and the normative assumption of the compliance with constitutional identity claimed by Federal Constitutional Court of Germany - Henkele, Olga Karlīne (Riga Graduate School of Law, 2019)
The requirement for the European Union to respect the national identities of its Member States nowadays enshrined in Article 4(2) of Treaty on European Union has boosted various debates about the meaning of the ‘national identity’. Moreover, the notion of national identity is often seen tightly interconnected with constitutional identity. While strictly speaking exactly the national identity was addressed in the Treaties, there are attempts to address the constitutional identity in the light of the identity clause. The thesis aims to analyse the meaning and scope of the national identity clause by concentrating not only on Article 4(2) of Treaty on European Union but also to determine the main aspects and elements of both concepts. Regardless of whether national or constitutional identity is addressed, the idea of both concepts is crucial to discuss in order to understand the patterns of the European constitutionalism and the growing role of the European integration in the European Union.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Public law::Constitutional law; Germany